Developing a blueprint for a civilian-military collaborative program in trauma training for Northern European countries: A South African experience. Issue 1 (January 2020) - van der Wal, Henk; van Dongen, Thijs T.C.F.; Vermeulen, Christine F.W.; Bruce, John L.; Bekker, Wanda; Manchev, Vassil; Kong, Victor; van Waes, Oscar; Clarke, Damian L.; Hoencamp, Rigo
Highlights: Rise of sub specialisation and low violence-related penetrating injuries in European cities require sufficient exposure A 'golden standard' of international collaboration programs does not exist A South African – European collaborative program creates a platform for trauma electives and training & teaching Collaboration shows overlapping benefits like social responsibility and exchange of knowledge and experience South African and military medical perspectives are reinforcing factors to improve acute care and medical leadership domains Abstract: Background: Recent terrorist attacks and mass shooting incidents in major European and North American cities have shown the unexpected influx of large volumes of patients with complex multi-system injuries. The rise of subspecialisation and the low violence-related penetrating injuries among European cities, show the reality that most surgical programs are unable to provide sufficient exposure to penetrating and blast injuries. The aim of this study is to describe and create a collaborative program between a major South African trauma service and a NATO country military medical service, with synergistic effect on both partners. This program includes comprehensive cross-disciplinary training & teaching, and scientific research. Methods: This is a retrospective descriptive study. The Pietermaritzburg hospital and Netherlands military trauma register databases were used for analysing patient data: Pietermaritzburg between September 2015 and August 2016, Iraq between May and July 2018 and Afghanistan from 2006 to 2010. Interviews were held to analyse the mutual benefits of the program. Results: From the Pietermaritzburg study, mutual benefits focus on social responsibility, exchange of knowledge and experience and further mutual exploration. The comparison showed the numbers of surgical procedures over a one-month period performed in Iraq 12.7, in Afghanistan 68.8 and in Pietermaritzburg 152. Conclusion: This study has shown a significant volume of penetrating trauma in South Africa, that can provide substantial exposure over a relatively short period. This help to prepare civilian and military surgeons and deployable military medical personnel for casualties with blast – and/or penetrating injuries. The aforementioned findings and the willingness to shape the mutual benefits, create a platform for trauma electives, research, education and training.